Modifikasi Mesin Produksi untuk Peningkatan Produktivitas dan Kualitas Produk di Umkm Bumbu Masak Buya - Arief, Dodi Sofyan; Badri, Muftil; Saputra, Sukemi Indra; Susilawati, Anita; Dalil, M. (LPPM UMRI, 2024)
This community service aims to improve productivity, the efficiency and quality the spice production process at Bumbu Masak Buya, a small and medium-sized enterprise (SME) in Dumai, Indonesia. The primary focus is on upgrading outdated production machinery, specifically roasters, grinders, dryers, and sieves. By modifying or redesigning these machines, the study seeks to improve their performance, durability, and safety. A combined qualitative and quantitative research methodology was employed. The initial step involves a comprehensive assessment of the current production process to identify areas for improvement. Subsequently, the design and implementation of machine modifications were undertaken. It involves a detailed assessment of the current production process, followed by the design and implementation of machine modifications. The impact of these modifications was evaluated to measure their effectiveness in enhancing productivity and product quality. The findings of this study are expected to provide valuable insights for other SMEs in the spice processing industry. By adopting similar strategies of machine modification, these SMEs can improve their operational efficiency, reduce production costs, and enhance the quality of their products.